John Heyl Vincent correspondence - Vincent, John Heyl, 1832-1920.
ALS from Vincent to William F. Sherwin regarding the schedule for upcoming lectures.
Methodist bishop and founder of the Chautauqua Assembly.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Sherwin, William F. -- 1826-1888 -- Correspondence; Chautauquas; Authors; Clergy